Peningkatan Kinerja Melalui Merger Dan Akuisisi - Putra, I Nyoman Nugraha Ardana; Sukendri, Nengah (Guna Sewaka, 2022)
The realignment of restructuring the company`s capital structure can execute through mergers and acquisitions. This research aim is to review the importance of merger activity and investment in terms of objectives and benefits. Methods used a literature review and secondary data. The research suggests that a company merger and acquisition support operation. There is good financial synergy and diversification, achieves economy of scale and scope that leads to cost efficiency and profitability, can obtain management skills, improve market forces, and may also be tax benefits. Because of that, the merger and acquisition were selective to enhance the company`s performance.